PENGARUH PEMBELAJARAN DENGAN PENILAIAN SECARA TRANSPARAN TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS XII IPA SMA - Waluyo, Sugeng Puji; Halini, Halini; Bistari, Bistari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was conducted on XII IPA 1 and XII IPA 3 students of SMA Negeri 3 Pontianak in academic year 2013/2014. It is based on average score differences of two different subjects in XI IPA class from previous academic year. The problem found in this research was because one of the subjects’ teacher used the transparency in evaluation. Quasi experiment by using transparency in evaluation was conducted on the second semester in sequences and series material in order to find out and describe the differences of students’ evaluation result between the experiment class and control class. Based on research findings, the students’ average score increased 7,23. Then based on student’s final test from both experiment and control class, it was found that t score < t table tabel (1,250 < 2,009) which means there was no differences between experiment and control class. Moreover, based on score difference analysis from both classes, it was found that t score < t tabel (0,621 < 2,009). It can be concluded that treatment does not give effect on students’ result where the size effect 0,183 and categorized as low.Keywords: Effect, Evaluation, Transparency